Planejamento das ações em saúde da família: desvelando cenários - Martins, Sharon da Silva (2021)
Health planning is still an incipient practice in health services in Brazil, although several studies prove its relevance to the reorientation of the health care model according to the principles of the Unified Health System. This study aimed to analyze the planning process of the actions developed by the Family Health teams in Santa Maria – RS. This is a qualitative, descriptive and exploratory study, whose population consisted of members from different sectors related to the management of the Municipal Health Department, the Municipal Health Council and workers of the Family Health teams, totaling 35 subjects. Data collection occurred in July and August 2020. It was done through documental analysis of the municipal SUS planning instruments and semi-structured interview, with scripts adapted to the different functions - assistance, management and social control. The data exploration was based on Bardin's content analysis. Results: The planning process presents weaknesses, such as the low participation of the community, the distance between those who plan and who performs the actions, lack of theoretical and methodological framework, fragmentation of the RAS, scarcity of human and material resources. There are potentials, such as the attempt to approach management with the eSF, reporting to monitor actions, workers with technical qualification and committed to improving the health of the community assisted; experiences of matrix support by NASF-AB and institutional by NEPeS and educational institutions. Studies and advances in practices are still needed, but the interviewed subjects believe that it is possible to improve what is instituted.